Spiritual health from the perspective of Nahj al-Balagha statements - Masoud Nakhaei Moghadam; Mahdi Fani (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. In this study, according to the words of Imam Ali(as) in  Nahj al-Balagha is attempted to achieve a sense of spiritual health. For this purpose, it was focused on the use of the health word in this collection and found physical (physical) and spiritual health is considered. Since the word "spirituality" was not used in  Nahj al-Balagha, inevitably we referred to the words of the Nahj al-Balagha commentators and found this term is commonly used in the mystical, moral and religious aspects. And partly this application can be seen in the words of non-Islamic researchers, then in the end, it is likely that spiritual health, a set of "true beliefs with respect for moral values" have been augmented.  Keywords: Spiritual Health, Nahj al-Balagha, Statements For downloading the full-text of this article please click here.